Skip to content Skip to sidebar Skip to footer

Geometric Progression : Problems and Solutions -Part (1)






Definition: Geometric Progression


A geometric progression is a sequence in which the ratio of each term to the one before it, is a constant.



ကိန်းစဉ်တစ်ခု၏ နီးစပ် (ကပ်လျက်) ကိန်းနှစ်လုံး (နောက်ကိန်းနှင့် ရှေ့ကိန်း)၏ အချိုးသည် ကိန်းသေဖြစ်လျှင် ၎င်းကိန်းစဉ်ကို
geometric progression ဟုခေါ်သည်။


This ratio is called the common ratio and is denoted by $r$.



If If $u_{1}, u_{2}, u_{3}, \ldots, u_{n-1}, u_{n}$ is an G.P.,
then $\dfrac{u_{2}}{u_{1}}=\dfrac{u_{3}}{u_{2}}=\ldots=\dfrac{u_{n}}{u_{n-1}}=$ constant.


$\dfrac{u_{n}}{u_{n-1}}=r$ and $u_{n}=u_{n-1} \cdot r$ where $r$ is called the common ratio.


If the first term is $a$, the the sequence may be $a, ar, ar^2, ar^3, \ldots$.


Hence the $n^{\text{th}}$ term is,





$\begin{array}{|l|}\hline
u_n = ar^{n-1}\\
\hline
\end{array}$









Definition: Geometric Mean (G.M.)


In a finite geometric progression, the terms between the first term and the last term are called the geometric means.



အဆုံးရှိ geometric progression တစ်ခု၏ ရှေ့ဆုံးကိန်းနှင့် နောက်ဆုံးကိန်းကြားရှိ ကိန်းများအားလုံးကို geonetric means (G.M) ဟုခေါ်သည်။


If $u_{1}, u_{2}, u_{3}, \ldots u_{n-1}, u_{n}$ is an G.P., then


$u_{2}, u_{3}, \ldots, u_{n-1}$ are called geometric means.


The geometric mean between two numbers $x$ and $y$ is given by





$\begin{array}{|l|}\hline
\text{G.M } = \sqrt{xy}\\
\hline
\end{array}$






Exercises





  1. Find

    (a) the common ratio,

    (b) the $10^{\text {th }}$ term and

    (c) the $n^{\text {th }}$ term of the following G.P.


    (i) $4,2,1, \dfrac{1}{2}, \ldots$


    (ii) $-2,4,-8,16, \ldots$


    (iii) $5,20,80,320, \ldots$


    (iv) $\dfrac{1}{3},-\dfrac{1}{9}, \dfrac{1}{27},-\dfrac{1}{81}, \ldots$


    (v) $\dfrac{8}{9}, \dfrac{4}{3}, 2,3, \ldots$


    (vi) $x^{5}, x^{4} y, x^{3} y^{2}, x^{2} y^{3}, \ldots$









  2. =======Sol 1=======




  3. If $3, x, y, z, w$ and 3072 are consecutive terms of a G.P.,
    find the value of $x$, $y, z$ and $w$.









  4. $3, x, y, z, w, 3072$ is a G.P.


    $\begin{aligned}
    & \\
    \therefore\ &a=3 \text{ and }\\\\
    &u_{6}=3072\\\\
    &a r^{5}=3072\\\\
    &3 r^{5}=3072\\\\
    &r^{5}=1024\\\\
    & r=(4)^{5} \\\\
    & r= 4\\\\
    \therefore\ &x=u_{2}=a r=12 \\\\
    & y=u_{3}=a r^{2}=48 \\\\
    & z=u_{4}=a r^{3}=192 \\\\
    & w=u_{5}=a r^{4}=768
    \end{aligned}$




  5. The second term of a G.P. is 64 and the fifth term is 27 .
    Find the first 6 terms of the G.P.









  6. In a G.P.,


    $u_{2}=64$


    $a r=64 \ldots(1)$


    $u_{5}=27$


    $a r^{4}=27 \ldots(2)$


    $(2) \div(1)$


    $\dfrac{a r^{4}}{a r}=\dfrac{27}{64}$


    $r^{3}=\left(\dfrac{3}{4}\right)^{3}$


    $r=\dfrac{3}{4}$


    $\therefore\ a\left(\dfrac{3}{4}\right)=64$


    $\therefore\ a=\dfrac{256}{3}$


    $\begin{aligned}
    \therefore\ u_{1} &=a=\dfrac{256}{3} \\\\
    u_{2} &=a r=64 \\\\
    u_{3} &=a r^{2}=48 \\\\
    u_{4} &=a r^{3}=36 \\\\
    u_{5} &=a r^{4}=27 \\\\
    u_{6} &=a r^{5}=\dfrac{81}{4}
    \end{aligned}$




  7. Find the $10^{\text {th }}$ term of the G.P.
    $a^{5}, a^{4} b, a^{3} b^{2}, a^{2} b^{3}, \ldots$.
    Which term of the G.P. is $\dfrac{b^{20}}{a^{15}} ?$









  8. $a^{5}$, $a^{4} b$, $a^{3} b^{2}$, $a^{2} b^{3}$, $\ldots$ is a GP.


    Let the first term be $A$ and the common ratio be $r$.
    Then,


    $\begin{aligned}
    &A=a^{5} \\\\
    &r=\dfrac{a^{4} b}{a^{5}}=\dfrac{b}{a}
    \end{aligned}$


    Let $\dfrac{b^{20}}{a^{15}}$ be the $n^{\text {th }}$ term.


    $\begin{aligned}
    \therefore u_{n} &=\dfrac{b^{20}}{a^{15}} \\\\
    A r^{n-1} &=\dfrac{b^{20}}{a^{15}} \\\\
    a^{5}\left(\dfrac{b}{a}\right)^{n-1} &=\dfrac{b^{20}}{a^{15}} \\\\
    \left(\dfrac{b}{a}\right)^{n-1} &=\left(\dfrac{b}{a}\right)^{20}\\\\
    \therefore\ n-1 &=20 \\\\
    n &=21 \\\\
    \therefore\ u_{21}&=\frac{b^{20}}{a^{15}}
    \end{aligned}$




  9. The $4^{\text {th }}$ term of the G.P is 3 and the sixth term is 147 .
    Find the first three terms of the two possible geometric progressions.









  10. In a G.P.,


    $\begin{aligned}
    u_{4}&=3\\\\
    a r^{3}&=3 \ldots(1)\\\\
    u_{6}&=147\\\\
    a r^{5}&=147 \ldots(2)\\\\
    (2) \div &(1)\\\\
    \dfrac{a r^{5}}{a r^{3}}&=\dfrac{147}{3}\\\\
    r^{2} &=49 \\\\
    r &=\pm 7 \\\\
    \text { When } r &=-7 \\\\
    a(-7)^{3} &=3 \\\\
    a &=-\dfrac{3}{343} \\\\
    \therefore\ u_{1}&=a=-\dfrac{3}{343} \\\\
    u_{2}&=a r=\dfrac{3}{49} \\\\
    u_{3}&=a r^{2}=-\dfrac{3}{7}\\\\
    \text { When } r &=7 \\\\
    a(7)^{3} &=3 \\\\
    a &=\dfrac{3}{343} \\\\
    \therefore \quad u_{1} &=a=\dfrac{3}{343} \\\\
    u_{2} &=a r=\dfrac{3}{49} \\\\
    u_{2} &=a r^{2}=\dfrac{3}{7}
    \end{aligned}$





  11. The product of the first three terms of the G.P. is 1 and the product of the third,
    fourth and the fifth term is $11 \dfrac{25}{64}$. Find the fifth term of the G.P.









  12. Let the given G.P. be $a, a r, a r^{2}, a r^{3}, a r^{4}, \ldots$


    By the problem,


    $\begin{aligned}
    a \cdot a r \cdot a r^{2} &=1 \\\\
    (a r)^{3} &=1 \\\\
    a r &=1 \\\\
    a &=\dfrac{1}{r}\\\\
    a r^{2} \cdot a r^{3} \cdot a r^{4} &=11 \dfrac{25}{64} \\\\
    a^{3} r^{9} &=\dfrac{729}{64} \\\\
    \dfrac{1}{r^{3}} \cdot r^{9} &=\dfrac{729}{64} \\\\
    r^{6} &=\dfrac{729}{64} \\\\
    r^{6} &=\left(\pm \dfrac{3}{2}\right)^{6}\\\\
    \therefore r &=\pm \dfrac{3}{2} \\\\
    a &=\dfrac{1}{r} \\\\
    \therefore a &=\pm \dfrac{2}{3} \\\\
    u_{5} &=a r^{4} \\\\
    &=\pm \dfrac{2}{3}\left(\pm \dfrac{3}{2}\right)^{4} \\\\
    &=\pm \dfrac{27}{8}
    \end{aligned}$




  13. Find two different values of $x$, so that $-\dfrac{3}{2}, x,-\dfrac{8}{27}$ will be a G.P.









  14. $\begin{aligned}
    \text { If }-\dfrac{3}{2}, x,-\dfrac{8}{27} &\text { is a G.P., then } \\\\
    \dfrac{x}{\left(-\dfrac{3}{2}\right)}&=\dfrac{\left(-\dfrac{8}{27}\right)}{x} \\\\
    \therefore\ x^{2}&=\dfrac{4}{9} \\
    x&=\pm \dfrac{2}{3}
    \end{aligned}$




  15. Find which term of the G.P.
    $\dfrac{8}{9}$, $\dfrac{4}{3} \sqrt{\dfrac{2}{3}}$, $\dfrac{4}{3}, \ldots$ is $\sqrt{6}$.









  16. $\dfrac{8}{9}$, $\dfrac{4}{3} \sqrt{\dfrac{2}{3}}$, $\dfrac{4}{3}$, $\ldots$, $\sqrt{6}$ is a G.P.


    $\begin{aligned}
    \therefore\ a &=\dfrac{8}{9} \\\\
    r &=\dfrac{\dfrac{4}{3}}{\dfrac{4}{3} \sqrt{\dfrac{2}{3}}}=\sqrt{\dfrac{3}{2}}\\\\
    \text{Let } u_{n}&=6, \text{then }\\\\
    \therefore\ a^{n-1}&=\sqrt{6}\\\\
    \dfrac{8}{9}\left(\sqrt{\dfrac{3}{2}}\right)^{n-1} &=\sqrt{6} \\\\
    \left(\sqrt{\dfrac{3}{2}}\right)^{n-1} &=\dfrac{9 \sqrt{6}}{8} \\\\
    &=\sqrt{\dfrac{9 \times 9 \times 6}{8 \times 8}} \\\\
    &=\sqrt{\dfrac{3^{5}}{2^{5}}} \\\\
    &=\left(\sqrt{\dfrac{3}{2}}\right)^{5}\\\\
    \therefore\ n-1 &=5 \\\\
    n &=6 \\\\
    \therefore\ u_{6} &=\sqrt{6}
    \end{aligned}$





  17. If $a, b, c, d$ is a G.P., show that $a^{2}-b^{2}$, $b^{2}-c^{2}$, $c^{2}-d^{2}$
    is also a G.P.









  18. $a, b, c, d$ is a G.P.


    Let the common ratio be $r$, then


    $\begin{aligned}
    a&=a \\\\
    b&=a r \\\\
    c&=a r^{2} \\\\
    d&=a r^{3}\\\\
    \dfrac{b^{2}-c^{2}}{a^{2}-b^{2}} &=\dfrac{a^{2} r^{2}-a^{2} r^{4}}{a^{2}-a^{2} r^{2}} \\\\
    &=\dfrac{r^{2}\left(a^{2}-a^{2} r^{2}\right)}{a^{2}-a^{2} r^{2}} \\\\
    &=r^{2} \\\\
    \dfrac{c^{2}-d^{2}}{b^{2}-c^{2}} &=\dfrac{a^{2} r^{4}-a^{2} r^{6}}{a^{2} r^{2}-a^{2} r^{4}} \\\\
    &=\dfrac{r^{2}\left(a^{2} r^{2}-a^{2} r^{4}\right)}{a^{2} r^{2}-a^{2} r^{4}} \\\\
    &=r^{2}\\\\
    \therefore\ \dfrac{b^{2}-c^{2}}{a^{2}-b^{2}}&=\dfrac{c^{2}-d^{2}}{b^{2}-c^{2}}
    \end{aligned}$


    $\therefore\ a^{2}-b^{2}, b^{2}-c^{2}, c^{2}-d^{2}$ is a G.P.




  19. If $a, b, c, d$ is a G.P., show that


    (i) $\dfrac{b+c}{c+d}=\dfrac{a+c}{b+d}$.


    (ii) $(a+d)(b+c)-(a+c)(b+d)=(b-c)^{2}$.









  20. $a, b, c, d$ is $a G . P .$


    Let the common ratio be $r$, then


    $\begin{aligned}
    a&=a \\\\
    b&=a r \\\\
    c&=a r^{2} \\\\
    d&=a r^{3}\\\\
    \text { (i) }\quad
    \dfrac{b+c}{c+d} &=\dfrac{a r+a r^{2}}{a r^{2}+a r^{3}} \\\\
    &=\dfrac{a r+a r^{2}}{r\left(a r+a r^{2}\right)} \\\\
    &=\dfrac{1}{r} \\
    \dfrac{a+c}{b+d} &=\dfrac{a+a r^{2}}{a r+a r^{3}} \\\\
    &=\dfrac{a+a r^{2}}{r\left(a+a r^{2}\right)} \\\\
    &=\dfrac{1}{r}\\\\
    \therefore\ \dfrac{b+c}{c+d}&=\dfrac{a+c}{b+d} \\\\
    \text { (ii) }\quad\quad\quad &(a+d)(b+c)-(a+c)(b+d) \\\\
    =\ & a b+a c+b d+c d-a b-a d-b c-c d \\\\
    =\ & a c+b d-a d-b c \\\\
    =\ & a\left(a r^{2}\right)+(a r)\left(a r^{3}\right)-a\left(a r^{3}\right)-(a r)\left(a r^{2}\right) \\\\
    =\ &(a r)^{2}+\left(a r^{2}\right)^{2}-2 a^{2} r^{3} \\\\
    =\ &(a r)^{2}-2(a r)\left(a r^{2}\right)+\left(a r^{2}\right)^{2} \\\\
    =\ & b^{2}-2 b c+c^{2} \\\\
    =\ &(b-c)^{2}
    \end{aligned}$




  21. If $a, b, c$ is an A.P. and $x, y, z$ is a G.P.,
    show that $x^{b-c} y^{c-a} z^{a-b}=1$.









  22. $a, b, c$ is an $A P$.


    Let $d$ be the common difference.


    $\begin{aligned}
    \therefore a =\ &a \\\\
    b &= a+d \\\\
    c &= &a+2 d
    \end{aligned}$



    $x, y, z$ is a G.P


    Let $r$ be the common ratio.



    $\begin{aligned}
    \therefore x =\ &x \\\\
    y =\ &x r \\\\
    z =\ &x r^{2} \\\\
    & x^{b-c} y^{c-a} z^{a-b} \\\\\
    =\ &x^{a+d-a-2 d}(x r)^{a+2 d-a}\left(x r^{2}\right)^{a-a-d} \\\\
    =\ &x^{-d} \cdot x^{2 d} \cdot r^{2 d} \cdot x^{-d} \cdot r^{-2 d} \\\\
    =\ &x^{0} r^{0} \\\\
    =\ &1
    \end{aligned}$



  23. In a G.P. the product of any three consecutive terms is $512$ .
    When 8 is added to the first term and $6$ to the second, then the
    terms form an A.P. Find the terms of the G.P.









  24. Let $a$, ar, ar be ginen G.P., then


    $\begin{aligned}
    &a \cdot a r \cdot a r^{2}=512 \\\\
    &(a r)^{3}=8^{3} \\\\
    &a r=8 \\\\
    &a=\dfrac{8}{r}
    \end{aligned}$


    $\therefore$ The terms of given G.P. are $\dfrac{8}{r}, 8,8 r .$


    By the problem,


    $\begin{aligned}
    \dfrac{8}{r}+8,(8+6), 8 r & \text { is an AP. } \\\\
    \therefore 14-\dfrac{8}{r}-8 &=8 r-14 \\\\
    6-\dfrac{8}{r}&=8 r-14 \\\\
    6 r-8&=8 r^{2}-14 r \\\\
    8 r^{2}-20 r+8&=0 \\\\
    2 r^{2}-5 r+2&=0 \\\\
    (2 r-1)(r-2)&=0\\\\
    \end{aligned}$


    $\therefore r=\dfrac{1}{2}$ or $r=2$.


    When $r=\dfrac{1}{2}$


    the terms of G.P ane $16,8,4$.


    When $r=2$,


    the terms of G.P. are $4,8,16$.




  25. In a G.P. the product of any three consecutive terms is $216$ .
    When 1 is added to the first term and $2$ to the second, then the
    terms form an A.P. Find the terms of the G.P.









  26. Let $a$, ar, ar be ginen G.P., then


    $\begin{aligned}
    &a \cdot a r \cdot a r^{2}=216 \\\\
    &(a r)^{3}=6^{3} \\\\
    &a r=8 \\\\
    &a=\dfrac{6}{r}
    \end{aligned}$


    $\therefore$ The terms of given G.P. are $\dfrac{6}{r}, 6,6 r .$


    By the problem,


    $\begin{aligned}
    \dfrac{6}{r}+1,(6+2), 6 r & \text { is an AP. } \\\\
    \therefore 8-\dfrac{6}{r}-1 &=6 r-8 \\\\
    7-\dfrac{6}{r}&=6 r-8 \\\\
    7 r-6&=6 r^{2}-8 r \\\\
    6 r^{2}-15 r+6&=0 \\\\
    2 r^{2}-5 r+2&=0 \\\\
    (2 r-1)(r-2)&=0\\\\
    \end{aligned}$


    $\therefore r=\dfrac{1}{2}$ or $r=2$.


    When $r=\dfrac{1}{2}$


    the terme of G.P ane $12,6,3$.


    When $r=2$,


    the terms of G.P. are $3,6,12$.




  27. $8, x, y$ are three consecutive terms of an A.P. while $x, y, 36$
    are three consecutive terms of a G.P., find the possible
    values of $x$ and $y$.









  28. $8, x, y$ is an A.P.


    $\begin{aligned}
    \therefore\ x -8 & =y-x \\\\
    y &=2 x-8 \\\\
    &=2(x-4)--(1) \\\\
    x, y &, 36 \text { is a G.P. } \\\\
    \dfrac{y}{x} &=\dfrac{36}{y} \\\\
    \therefore\ y^{2} &=36 x-(2)
    \end{aligned}$


    Substituting $y=2 x-8$ in equation (2),


    $\begin{aligned}
    4(x-4)^{2} &=36 x \\\\
    x^{2}-8 x+16 &=9 x \\\\
    x^{2}-17 x+16 &=0 \\\\
    \therefore\ (x-1)(x-16) &=0 \\\\
    x=1 \text { or } x &=16
    \end{aligned}$


    When $x=1, y=2(1-4)=-6$


    When $x=16, y=2(16-4)=24$





  29. In a G.P., whose first term is positive, the sum of the first and
    the third term is $\dfrac{13}{9}$ and the product of the second and
    fourth term is $\dfrac{16}{81}$. Find the common ratio and
    the $6^{\text {th }}$ term.









  30. Let $a$, ar, $a r^{2}$ be given GI.P., where $a>0$.


    By the problem,


    $\begin{aligned}
    a+a r^{2}&=\dfrac{13}{9} \ldots (1)\\\\
    ar \cdot ar^{2}&=\dfrac{16}{81}\\\\
    \left(a r^{2}\right)^{2}&=\dfrac{16}{81}\\\\
    \therefore\ a r^{2}&=\dfrac{4}{9} \left(\because a>0 \text { and } r^{2}>0\right)\ldots(2)
    \end{aligned}$


    Substituting $a r^{2}=\dfrac{4}{9}$ in equation $(1)$,


    $\begin{aligned}
    a+\dfrac{4}{9} &=\dfrac{13}{9} \\\\
    a &=1\\\\
    \therefore 1\left(r^{2}\right) &=\dfrac{4}{9} \\\\
    r &=\pm \dfrac{2}{3}
    \end{aligned}$


    When $a=1$, and $r=-\dfrac{2}{3}$,


    $\begin{aligned}
    u_{6} &=a r^{5} \\\\
    &=1\left(-\dfrac{2}{3}\right)^{5} \\\\
    &=-\dfrac{32}{243}
    \end{aligned}$


    When $a=1$, and $r=\dfrac{2}{3}$


    $\begin{aligned}
    u_{6} &=a r^{5} \\\\
    &=1\left(\dfrac{2}{3}\right)^{5} \\\\
    &=\dfrac{32}{243}
    \end{aligned}$




  31. If $\log _{3} 2$, $\log _{4} x$, $\log _{2} 81$ is a G.P.
    then find the possible values of $x$.









  32. $\log _{3} 2, \log _{4} x, \log _{2} 81$ is a G.P.


    $\begin{aligned}
    \therefore\ \dfrac{\log _{4} x}{\log _{3} 2} &=\dfrac{\log _{2} x}{\log _{4} x} \\\\\
    \therefore\ \left(\log _{4} x\right)^{2} &=\log _{2} 81 \times \log _{3} 2 \\\\\
    &=4 \log _{2} 3 \times \dfrac{1}{\log _{2} 3}\\\\\
    \left(\log _{4} x\right)^{2}&=4 \\\\\
    \therefore\ \log _{4} x&=\pm 2 \\\\\
    \therefore\ x &=4^{-2} \text { or } x=4^{2} \\\\\
    x &=\dfrac{1}{16} \text { or } x=16
    \end{aligned}$





  33. If $\dfrac{1}{b+a}, \dfrac{1}{2 b}$ and $\dfrac{1}{b+c}$ are in A.P.,
    prove that $a, b$ and $c$ are in G.P.









  34. $\begin{aligned}
    \dfrac{1}{b+a}, \dfrac{1}{2 b}, \dfrac{1}{b+c}\ & \text {is an A.P } \\\\\
    \therefore \dfrac{1}{2 b}-\dfrac{1}{b+a} &=\dfrac{1}{b+c}-\dfrac{1}{2 b} \\\\\
    \dfrac{b+a-2 b}{2 b(b+a)} &=\dfrac{2 b-b-c}{2 b(b+c)} \\\\\
    \dfrac{a-b}{a+b} &=\dfrac{b-c}{b+c}\\\\\
    \text {By Componendo} &- \text {Dividendo}\\\\
    \dfrac{(a-b)+(a+b)}{(a-b)-(a+b)} &=\dfrac{(b-c)+(b+c)}{(b-c)-(b+c)} \\\\\
    -\dfrac{2 a}{2 b} &=-\dfrac{2 b}{2 c} \\\\\
    \dfrac{a}{b} &=\dfrac{b}{c} \\\\\
    \therefore \dfrac{b}{a} &=\dfrac{c}{b}\\\\\
    \therefore a, b, c & \text { are in G.P.}
    \end{aligned}$





  35. In a G.P., the first term exceeds the third term by $72$ and the sum
    of the second and third term is $36$ . Find the first term.









  36. Let $a$, $ar$, $ar^{2}$ be given G.P.


    By the problem,



    $\begin{aligned}
    a-a r^{2}&=72 \\\\
    a\left(1-r^{2}\right)&=72\ldots(1) \\\\
    a r+a r^{2}&=36 \\\\
    a r(1+r)&=36 \ldots(2)\\\\
    (1) \div(2) & \\\\
    \dfrac{a\left(1-r^{2}\right)}{\operatorname{ar}(1+r)} &=\dfrac{72}{3 b} \\\\
    \dfrac{(1-r)(1+r)}{r(1+r)} &=2 \\\\
    \therefore \quad 1-r &=2 r \\\\
    3 r &=1 \\\\
    r &=\dfrac{1}{3}\\\\
    \text{Substituting } r=\dfrac{1}{3}& \text{ in equation} (1),\\\\
    a\left(1-\dfrac{1}{9}\right)=72 \\\\
    \dfrac{8 a}{9}=72 \\\\
    a=81
    \end{aligned}$




  37. The fourth term of a G.P. is $9$ and the ninth term is $2187$.
    Find the first 4 terms of the G.P.









  38. $\begin{aligned}
    \text{In a G.P, } & \\\\
    u_{4}&=9 \\\\
    a r^{3}&=9\ldots(1) \\\\
    u_{9}&=2187 \\\\
    a{r}^{8}&=2187\ldots(2) \\\\
    (2) \div(1),& \\\\
    \dfrac{a r^{8}}{a r^{3}}&=\dfrac{2187}{9}\\\\
    r^{5}&=243 \\\\
    r^{5}&=3^{5} \\\\
    r&=3
    \end{aligned}$


    Substituting $r=3$ in equation (1),


    $\begin{aligned}
    a\left(3^{3}\right)&=9 \\\\
    a&=\dfrac{1}{3}\\\\
    \therefore\ u_{1} &=a=\dfrac{1}{3} \\\\
    u_{2} &=a r=1 \\\\
    u_{3} &=a r^{2}=3 \\\\
    u_{4} &=a^{3}=9
    \end{aligned}$




  39. The fourth term of a G.P. exceeds the third by $\dfrac{3}{44}$ and the third
    term exceeds the second term by $\dfrac{1}{22}$. Find the first term and
    the sixth term of the G.P.









  40. In a G.P,


    $\begin{aligned}
    u_{4}-u_{3}&=\dfrac{3}{44} \\\\
    a r^{3}-a r^{2}&=\dfrac{3}{44} \\\\
    a r^{2}(r-1)&=\dfrac{3}{44}\ldots(1)\\\\
    u_{3}-u_{2} &=\dfrac{1}{22} \\\\
    {ar}^{2}-a r &=\dfrac{1}{22} \\\\
    {ar}(r-1) &=\dfrac{1}{22}\ldots(2) \\\\
    (1) \div(2), & \\\\
    {ar}^{2}(r-1) & \\\\
    {ar}(r-1) &=\dfrac{1}{\dfrac{3}{22}}\\\\
    r &=\dfrac{3}{44} \times 22 \\\\
    &=\dfrac{3}{2}\\\\
    \end{aligned}$


    Substituting $r=\dfrac{3}{2}$ in equation (2),


    $\begin{aligned}
    \dfrac{3 a}{2}\left(\dfrac{3}{2}-1\right) &=\dfrac{1}{22} \\\\
    \dfrac{3 a}{4} &=\dfrac{1}{22} \\\\
    a &=\dfrac{2}{33} \\\\
    \therefore \quad u_{6} &=a r^{5} \\\\
    &=\left(\dfrac{2}{33}\right)\left(\dfrac{3}{2}\right)^{5} \\\\
    &=\dfrac{81}{176}
    \end{aligned}$




  41. Three consecutive terms of a G.P. are $3^{2 x-1}, 9^{x}$ and $243$ .
    Find the value of $x$. If $243$ is the fifth term of the G.P.,
    find the seventh term.









  42. $3^{2 x-1}, 9^{x}, 243$ are in a G.P.


    $\begin{aligned}
    \therefore\ \dfrac{9^{x}}{3^{2 x-1}} &=\dfrac{243}{9^{x}} \\\\
    \dfrac{3^{2 x}}{3^{2 x-1}} &=\dfrac{3^{5}}{3^{2 x}} \\\\
    3 &=3^{5-2 x} \\\\
    \therefore \quad 5-2 x &=1 \\\\
    x &=2\\\\
    \therefore\ u_{3} &=3^{4-1}=27 \\\\
    u_{4} &=9^{2}=81 \\\\
    u_{5} &=243 \\\\
    \therefore\ r &=\dfrac{81}{27} \\\\
    &=3 \\\\
    \therefore u_{7} &=a r^{6} \\\\
    &=\left(a r^{4}\right) r^{2} \\\\
    &=u_{5} \times r^{2}=243 \times 9=2187
    \end{aligned}$




  43. Find three numbers in a G.P. such that their sum is $42$ and
    their product is $512$.









  44. Let the three numbers in a G.P. be $a$, $ar$, $ar^2$.


    By the problem,


    $\begin{aligned}
    a+a r+a r^{2}&=42 \\\\
    a\left(1+r+r^{2}\right)&=42 \ldots(1)\\\\
    a\cdot ar \cdot ar^{2}&=512\\\\
    (a r)^{3}&=512\\\\
    a r&=8 \\\\
    a&=\dfrac{8}{r} \ldots(2)
    \end{aligned}$


    Substituting $a=\dfrac{8}{r}$ in equation (1).


    $\begin{aligned}
    \dfrac{8}{r}\left(1+r+r^{2}\right)&=42 \\\\
    4+4 r+4 r^{2}&=21 r \\\\
    4 r^{2}-17 r+4&=0 \\\\
    (4 r-1)(r-4)&=0\\\\
    \therefore\ r=\frac{1}{4} \text { or } r&=4
    \end{aligned}$


    When $r=\dfrac{1}{4}$,


    $a=\dfrac{8}{1/4}=32$


    Then three numbers are $32,8,2$.


    When $r=4$,


    $a=\dfrac{8}{4}=2$


    Then three numbers are $2,8,32$.




  45. Insert two geometric means between $2$ and $128$ .









  46. Let the required geometric means be $x$ and $y$,


    $\therefore 2, x, y, 128$ is a G.P.


    Let the common ratio be $r$.


    $\begin{aligned}
    \therefore\ 2 &=2 \\\\
    x &=2 r \\\\
    y &=2 r^{2} \\\\
    128 &=2 r^{2}\\\\
    \therefore\ r^{3} &=64 \\\\
    r &=4 \\\\
    \therefore\ x &=8 \\\\
    y &=32
    \end{aligned}$





  47. The ratios of two numbers is $9: 1$. The sum of the arithmetic
    mean and geometric mean between the two numbers is $96$ ,
    find the two numbers.









  48. Let the two numbers be $9 x$ and $x$.


    $\begin{aligned}
    \text { A.M between } 9 x \text { and } x&=\frac{9 x+x}{2}\\\\
    &=5 x \\\\
    \text { G.M between } 9 x \text { and } x&=\sqrt{9 x^{2}}\\\\
    &=3 x \\\\
    \text { A.M } + \text { G.M } &=96 \\\\
    5 x+3 x &=96 \\\\
    8 x &=96 \\\\
    x &=12 \\\\
    1^{\text {st} } \text {number } &=108 \\\\
    2^{\text {n d} } \text { number } &=12
    \end{aligned}$






  49. If the arithmetic mean between $x$ and $y$ is $15$ and the geometric mean
    is $9$ , find $x$ and $y$.









  50. $\begin{aligned}
    \text{A.M between } x \text{ and } y &=15\\\\
    \therefore \ \dfrac{x+y}{2} &=15 \\\\
    x+y &=30\ldots(1)\\\\
    \text{G.M between } x \text{ and } y = 9\\\\
    \therefore \ \sqrt{x y} &=9 \\\\
    x y &=81 \\\\
    y &=\dfrac{81}{x}\ldots(2)\\\\
    \text{Substituting } y=\dfrac{81}{x} &\text{ in equation } (1),\\\\
    x+\dfrac{81}{x}&=30 \\\\
    x^{2}+81&=30 x \\\\
    x^{2}-30 x+81&=0 \\\\
    (x-3)(x-27)&=0 \\\\
    x=3 \text { or } x&=27 \\\\
    \text { When } x=3, y&=\dfrac{81}{3}=27 \\\\
    \text { When } x=27, y&=\dfrac{81}{27}=3
    \end{aligned}$




  51. Show that the products of the corresponding terms of the sequences
    $a, a r, a r^{2}, \ldots, a r^{n-1}$ and $A, A R, A R^{2}, \ldots, A R^{n-1}$
    form a G.P, and find the common ratio.









  52. The first sequence is $a, a r, a r^{2}, \ldots, a r^{n-1}$.


    The second sequence is $A, A R, A R^{2}, \ldots, A R^{n-1}$.


    The sequence formed by the products of the corresponding terms of above sequences is $a A, a r A R, a r^{2} A R^{2}, \ldots, a r^{n-1} A R^{n-1}$.


    $\begin{aligned}
    &\frac{u_{2}}{u_{1}}=\frac{a r A R}{a A}=r R \\\\
    &\frac{u_{3}}{u_{2}}=\frac{a r^{2} A R^{2}}{a r A R}=r R
    \end{aligned}$



    $\therefore$ The ratio of any two successive terms is the same.


    $\therefore$ The products of the corresponding terms of the sequences $a, a r, a r^{2}, \ldots, a r^{n-1}$ and $A, A R, A R^{2}, \ldots, A R^{n-1}$ form a G.P.




  53. Given that $\dfrac{a+b x}{a-b x}=\dfrac{b+c x}{b-c x}=\dfrac{c+d x}{c-d x}$
    where $x \neq 0$, prove that $a, b, c, d$ are in G.P.









  54. $\begin{aligned}
    \text { Let } \dfrac{a+b x}{a-b x}&=\dfrac{b+c x}{b-c x}=\dfrac{c+d x}{c-d x}=k. \\\\
    \therefore\ a+b x &=k(a-b x) \\\\
    a+b x &=k a-k b x \\\\
    k b x+b x &=k a-a \\\\
    b x(k+1) &=a(k-1) \\\\
    \dfrac{b}{a} &=\dfrac{k-1}{(k+1) x} \\\\
    \text { Similarly, } & \\\\
    b+c x &=k(b-c x) \\\\
    b+c x &=k b-k c x \\\\
    k c x+c x &=k b-b \\\\
    c x(k+1) &=b(k-1)\\\\
    \dfrac{c}{b} & =\dfrac{k-1}{(k+1) x} \\\\
    \text { Again, } & \\\\
    c+d x & =k(c-d x) \\\\
    c+d x & =k c-k d x \\\\
    k d x+d x & =k c-c \\\\
    d x(k+1) & =c(k-1) \\\\
    \dfrac{d}{c} & =\dfrac{k-1}{(k+1) x} \\\\
    \therefore\ \dfrac{b}{a}=\dfrac{c}{b} & =\dfrac{d}{c} \\\\
    \therefore\ a, b, c, d & \text { is in a G.P.}
    \end{aligned}$




  55. If $a, b, c, d$ are in G.P., prove that $a+b, b+c$ and $c+d$ are also in G.P.









  56. $a, b, c, d$ are in G.P.


    Let the common ratio be $r$.


    $\begin{aligned}
    \therefore a &=a \\\\
    b &=a r \\\\
    c &=a r^{2} \\\\
    d &=a r^{3} \\\\
    \dfrac{b+c}{a+b} &=\dfrac{a r+a r^{2}}{a+a r} \\\\
    &=\dfrac{r(a+a r)}{a+a r} \\\\
    &=r\\\\
    \dfrac{c+d}{b+c} &=\dfrac{a r^{2}+a r^{3}}{a r+a r^{2}} \\\\
    &=\dfrac{r\left(a r+a r^{2}\right)}{a r+a r^{2}} \\\\
    &=r \\\\
    \therefore\ \dfrac{b+c}{a+b} &=\dfrac{c+d}{b+c}\\\\
    \therefore\ a+b,\ & b+c,\ c+d \text{ are in G.P.}
    \end{aligned}$





  57. If $a, b, c$ are in A.P., show that $2^{a x+1}$, $2^{b x+1}$, $2^{c x+1}$
    are in G.P.









  58. $a, b, c$ are in A.P.


    Let the common difference be $d$.


    $\begin{aligned}
    \therefore a &=a \\\\
    b &=a+d \\\\
    c &=a+2 d \\\\
    \dfrac{2^{b x+1}}{2^{a x+1}} &=2^{(b-a) x}=2^{dx}\\\\
    \dfrac{2^{c x+1}}{2^{b x+1}} &=2^{(c-b) x}=2^{dx} \\\\
    \therefore\ \dfrac{2^{b x+1}}{2^{a x+1}}&=\dfrac{2^{c x+1}}{2^{b x+1}} \\\\
    \therefore\ 2^{a x+1},\ & 2^{b x+1},\ 2^{c x+1} \text { are in G.P. }
    \end{aligned}$




  59. The first three terms of an infinite geometric progression are $m-1,6, m+4$,
    where $m$ is an integer. Show that $m$ satisfies the equation $m^{2}+3 m-40=0$.
    Hence find the possible values of $m$ and the common ratio of the progression.









  60. \begin{aligned}
    m-1,\ 6,\ m+4,& \cdots \text { is a GP. } \\\\
    \therefore\ \dfrac{6}{m-1} &=\dfrac{m+4}{6} \\\\
    m^{2}+3 m-4 &=36 \\\\
    \therefore m^{2}+3 m-40 &=0 \\\\
    (m+8)(m-5) &=0 \\\\
    \therefore\ m=-8 \text { or } m &=5\\\\
    \text { When } m &=-8, \\\\
    \text { common ratio } &=\dfrac{6}{-8-1} \\\\
    &=-\dfrac{2}{3} \\\\
    \text { When } m &=5, \\\\
    \text { common ratio } &=\dfrac{6}{5-1} \\\\
    &=\dfrac{3}{2}
    \end{aligned}








Post a Comment for "Geometric Progression : Problems and Solutions -Part (1)"

Sponsored by: iklanvideo.io